2021
DOI: 10.1021/acsenergylett.0c02475
|View full text |Cite
|
Sign up to set email alerts
|

Halide Segregation in Mixed-Halide Perovskites: Influence of A-Site Cations

Abstract: Mixed-halide perovskites offer bandgap tunability essential for multijunction solar cells; however, a detrimental halide segregation under light is often observed. Here we combine simultaneous in situ photoluminescence and X-ray diffraction measurements to demonstrate clear differences in compositional and optoelectronic changes associated with halide segregation in MAPb(Br 0.5 I 0.5 ) 3 and FA 0.83 Cs 0.17 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
182
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 157 publications
(221 citation statements)
references
References 63 publications
(204 reference statements)
10
182
1
Order By: Relevance
“…The film was then exposed to the segregation-driving CW illumination and the measurements were repeated after stabilisation of the PL spectral changes, resulting in μ = 37.2 ± 0.6 cm 2 /(Vs) . Such similar μ values of charge carriers immediately after photoexcitation are consistent with halide segregation occurring only in a small portion of the film despite drastic changes in PL lineshape 2 , 9 , 17 , which results in the minimal impact of halide demixing on the charge transport properties of the majority phase. This finding agrees with our recent observations in a parallel study carried out on identical films, in which XRD diffraction showed good preservation of material crystallinity upon halide segregation 17 .…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…The film was then exposed to the segregation-driving CW illumination and the measurements were repeated after stabilisation of the PL spectral changes, resulting in μ = 37.2 ± 0.6 cm 2 /(Vs) . Such similar μ values of charge carriers immediately after photoexcitation are consistent with halide segregation occurring only in a small portion of the film despite drastic changes in PL lineshape 2 , 9 , 17 , which results in the minimal impact of halide demixing on the charge transport properties of the majority phase. This finding agrees with our recent observations in a parallel study carried out on identical films, in which XRD diffraction showed good preservation of material crystallinity upon halide segregation 17 .…”
Section: Resultssupporting
confidence: 69%
“…Such similar μ values of charge carriers immediately after photoexcitation are consistent with halide segregation occurring only in a small portion of the film despite drastic changes in PL lineshape 2 , 9 , 17 , which results in the minimal impact of halide demixing on the charge transport properties of the majority phase. This finding agrees with our recent observations in a parallel study carried out on identical films, in which XRD diffraction showed good preservation of material crystallinity upon halide segregation 17 . To understand the impact of heterogeneities on the transport properties, we tuned the OPTP photoexcitation wavelength to 720 nm.…”
Section: Resultssupporting
confidence: 69%
“…Although the resulting increased bandgaps lower the optical absorption, the stability of bromide-based perovskites is significantly enhanced [56] and this is confirmed by thermal decomposition of MAPbX 3 perovskites [57]. Furthermore, the stability seems to be also linked to the A-site cation mixture as observed in the case of halide segregation [58]. Using binary mixtures of the aforementioned seven A-site cations and three halogens we assemble the perovskite structures of formula A x A' 1−x PbX y X' z X" 3−y−z .…”
Section: Mixed-cation Mixed-halide Perovskitesmentioning
confidence: 78%
“…Moreover, in such a sequence of reducing dimensionality, we would expect diffraction of larger RDPs to be weaker, since there would initially be few instances of adjacent and periodic high-n RDPs, but once they split into lower-n RDPs, these structures would be immediately adjacent to each other, thus promoting diffraction 21 . Considering the small percentage of bromine in the (MAPbBr 3 ) 0.05 (FAPbI 3 ) 0.95 films, we posit that the difference in the 2D/3D transformation pathways arises due to the greater stability of FAPbI 3 compared to MAPbI 3 , where the latter is known to exhibit poorer thermal stability due to loss of volatile species under thermal stress and is more easily converted to PbI 2 26,27 .…”
Section: Dmentioning
confidence: 97%